Genetic conservation of breeding populations: Literature review from the perspective of species of the cerrado biome - Dias, Marcos Antônio Negreiros; Reis, Guilherme de Miranda Fernandes; Pereira, Ludmilla Morais; Gusmão, Ana Debora Ribeiro Cardoso; de Sousa, Iêdes Dias; dos Santos, André Ferreira (Seven Editora, 2024)
This work addresses the Genetic Conservation of Breeding Populations, focusing specifically on the species of the Cerrado biome. Using a qualitative approach and drawing on theoretical references, the research examined key concepts related to forest genetic conservation, genetic variability, conservation methods and the challenges faced in this context. The methodology employed involved a detailed bibliographic review and a critical analysis of the information collected in recent years. The efforts and cases of genetic conservation of some species of the cerrado were highlighted, despite the scarcity of studies in this field. The discussion raised the urgent need for more research and actions aimed at the conservation and improvement of the species of the cerrado biome, given their importance for biodiversity and their relevance for the maintenance of natural ecosystems. The study also addressed the advantages and disadvantages of different methods of genetic conservation, as well as future trends in this area. In short, the work offers a comprehensive view of the genetic conservation of cerrado species, highlighting the importance of their preservation for environmental sustainability and food security. DOI:https://doi.org/10.56238/sevened2024.023-012